Complementary Effects of Virus Population Are Required for Efficient Virus Infection - Sun, Yuechao; Zhang, Yu; Zhang, Xiaobo (Frontiers in Microbiology, 2022)
It is believed that the virions of a virus infecting a host may share the identical viral genome and characteristics. However, the role of genomic heterogeneity of the virions of a virus in virus infection has not been extensively explored. To address this issue, white spot syndrome virus (WSSV), a DNA virus infecting crustaceans, was characterized in the current study. In WSSV, differences in two nucleotides of the viral genome generated two types of WSSV, forming a virus population that consisted of Type A WSSV (encoding WSSV lncRNA-24) and Type B WSSV (encoding the wsv195 gene) at a ratio of 1:3. The virus populations in all virus-infected cells and tissues of different hosts exhibited a stable 1:3 structure. WSSV lncRNA-24 in Type A WSSV promoted virus infection by binding to shrimp and WSSV miRNAs, while the wsv195 gene in Type B WSSV played an essential role in virus infection. Loss of Type A WSSV or Type B WSSV in the WSSV population led to a 100-fold decrease in viral copy number in shrimp. Simultaneous loss of both types of WSSV prevented virus infection. These results indicated that the virus infection process was completed by two types of WSSV encoding different functional genes, revealing the complementary effects of WSSV population. Therefore, our study highlights the importance of the complementarity of virus population components in virus infection.